IMPLEMENTASI KEBIJAKAN RENCANA TATA RUANG WILAYAH TAHUN 2012-2032 DI KOTA BENGKULU - Novliza Eka Patrisia; Eva Oktarianti (UNIVED PRESS, Universitas Dehasen Bengkulu, 2019)
Implementation of spatial policy Bengkulu happened complex problems such as conflicts occur land, water shortages and land conversion. This research uses descriptive qualitative research approach. As the results show that: 1. Product policy Local Regulation number 14 in 2012 on Bengkulu Spatial Planning is good 2. Implementation of spatial policy Bengkulu is well enough but there are still some discrepancies that occur in the implementation. In the application of the Sustainable Urban Development concept is appropriate but the environmental issues become crucial issues encountered in the implementation of spatial policy in realizing about Sustainable Urban Development 3. The factors enabling in the implementation of spatial policy in Bengkulu are policy on Bengkulu spatial planning, socialization, liveliness implementor. While the factors inhibiting in this research are public awareness and land conversion.